Bosnian Croats in Croatia: 'Etnically Privileged Migrant, 'Culturaly Distant Co-ethnics' or 'Croats as any Other Croats'?' - Valenta, Marko; Strabac, Zan; Mesić, Milan, sociolog (2011)
Based on previous studies on Bosnian refugees around the world, the authors assume, that unlike other migrants in Croatia, Bosnian Croats in Croatia may be seen as 'co-ethnic migrants' or 'ethnically privileged migrants'. However, it is also assumed that Bosnian Croats in Croatia are defined in two diametrically different ways - as lw status, culturally distant co-ethnics and as Croats as any other Croats, which has resulted in a different positioning toward the mainstream society.
Projekt MZOS
ENG